Linear inverse association between prognostic nutritional index and colorectal cancer risk based on NHANES data - Youwei Han; Peng Zhou; Liping Wang; Yu Tang; Yuyan Ding; Yujiao Yang; Chen Qiu; Yuyang Li; Jiazeng Xia (Scientific Reports)
Abstract Despite the Prognostic Nutritional Index (PNI) serving as a crucial prognostic marker for predicting survival outcomes in cancer patients, its association with the risk of Colorectal Cancer (CRC) is not well comprehended. We hypothesized that lower PNI levels are associated with a higher risk of CRC. The datasets from the National Health and Nutrition Examination Survey (NHANES) spanning from 2007 to 2016 were employed in this study, incorporating data on demographics, laboratory tests, and questionnaires. Participants aged ≥ 20 years were included, while those with missing tumor history or incomplete laboratory data for PNI calculation (serum albumin or lymphocyte count) were excluded. A total of 26,229 participants who met the inclusion criteria were evaluated, of which 176 had a history of CRC. The PNI was calculated as 0.005 × absolute lymphocyte count + 10 × serum albumin, and categorized into quartiles. CRC status was determined via self-reported medical history. To investigate the linear relationship between PNI and CRC, multivariable logistic regression models, restricted cubic spline analysis, and subgroup analyses were used. Covariates were adjusted using multiple imputation, and all analyses were conducted using DecisionLinnc v1.0. Statistical significance was set at P < 0.05. The average PNI score was 42.55 ± 3.42. Fully adjusted multivariable logistic regression models identified a significant inverse relationship between higher PNI scores and lower odds of CRC. Specifically, each one-unit increase in PNI was associated with a 6.43% reduction in the odds of CRC [OR: 0.9357; 95% CI: 0.8942, 0.9807; p = 0.005]. Restricted cubic spline analysis further validated a linear association between PNI and CRC risk. Subgroup analyses demonstrated that the association remained consistent across factors including gender, age, marital status, education level, BMI, alcohol consumption, smoking habits, history of hypertension, hyperlipidemia, and diabetes. Males exhibited a more pronounced inverse correlation between PNI and CRC risk. Higher PNI scores are independently associated with reduced odds of CRC. PNI may serve as a valuable risk biomarker for identifying individuals at elevated CRC risk and could enhance large-scale screening strategies.